ECOLOGY AND BIOLOGY OF ABUDEFDUF GLAUCUS (CUVIER) (POMACENTRIDAE, PISCES) FROM MINICOY ATOLL, LAKSHADWEEP - Pillai, C S Gopinatha; Mohan, Madan (Indian Journal of Fisheries, 2011)
Studies on the ecology and biology of some reef fishes from Lakshadweep were inititated by the present authors during 1981-’83.